Respuesta :
Answer:
The correct option is C.
Step-by-step explanation:
The given expression is
[tex]x^2+16y^2[/tex]
In option A,
[tex](x+4y)(x+4y)=x^2+4xy+4xy+16y^2=x^2+8xy+16y^2[/tex]
Therefore option A is incorrect.
In option B,
[tex](x+4y)(x-4y)=x^2-4xy+4xy-16y^2=x^2-16y^2[/tex]
Therefore option B is incorrect.
In option D,
[tex](x-4y)(x-4y)=x^2-4xy-4xy-16y^2=x^2-8xy+16y^2[/tex]
Therefore option D is incorrect.
Since the given expression can not be factored further, therefore it is a prime expression and option C is correct.